2022
DOI: 10.1103/physrevd.106.082006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma noise in TianQin time-delay interferometry

Abstract: TianQin is a proposed geocentric space-based gravitational wave observatory mission, which requires time-delay interferometry (TDI) to cancel laser frequency noise. With high demands for precision, solar-wind plasma environment at ∼ 10 5 km above the Earth may constitute a nonnegligible noise source to laser interferometric measurements between satellites, as charged particles perturb the refractivity along light paths. In this paper, we first assess the plasma noises along single links from space-weather mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…As in the previous case of static gravity, we calculate the inter-satellite range-acceleration ASD from Eq. (42). At the same time, we obtain the numerical result from TQPOP in which the force models consist of the Earth's static gravity and the gravity change from the free oscillations mentioned above.…”
Section: Model Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the previous case of static gravity, we calculate the inter-satellite range-acceleration ASD from Eq. (42). At the same time, we obtain the numerical result from TQPOP in which the force models consist of the Earth's static gravity and the gravity change from the free oscillations mentioned above.…”
Section: Model Verificationmentioning
confidence: 99%
“…We calculate the TianQin's rangeacceleration time series using the numerical procedure and the analytical formula, respectively. Then we process the data with a high-pass filter [42] to extract signals of Earth's free oscillation induced by earthquake above 10 −4 Hz. The numerical and analytical waveforms are compared in Fig.…”
Section: Model Verificationmentioning
confidence: 99%
“…The result indicated that, the PSD of singlelink plasma noise based on the 572 daily measurements from Wind/SWE are lower than the single-link sensitivity requirements of LISA. In addition, in [16], the SWMF model and piecewise parabolic method with a Lagrangian remap-magnetohydrodynamic model were utilized to simulate plasma noise in the 10 −4 Hz-10 −1 Hz frequency band. It was demonstrated that plasma noise in this frequency band follows Kolmogorov spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that plasma noise in this frequency band follows Kolmogorov spectrum. Currently, most research on plasma noise in space-based GW detectors relies on numerical results [13,14,16]. The numerical simulation results are more realistic but also require more computational resources and are limited by the resolution of models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation